The Effectiveness of Audio-Visual Media on Changes In Knowledge, Attitudes, and Behavior of "Resti" Mothers to Use Contraception in Kramatwatu District, Serang Regency, Banten Province: Efektivitas Media Audio Visual terhadap Perubahan Pengetahuan, Sikap, dan Perilaku Ibu "Resti" Untuk Menggunakan Kontrasepsi di Kecamatan Kramatwatu Kabupaten Serang Provinsi Banten - Ade Handriati; Irfa Kartini; Rahayu (Jurnal Midwifery, 2024)
Introduction:. The highest number of maternal deaths in Banten is in Serang Regency, namely 66 cases of maternal death.(Rachmawati 2021). The highest cause of maternal mortality is pregnancy hypertension. Hypertension in pregnancy occurs in mothers with high risk age, so it is necessary to postpone or end the pregnancy at high risk age by using contraception. The purpose of this study was to determine the effectiveness of audio visual media on changes in knowledge, attitudes and behavior of mothers to use contraception. Method: This method of research is Quasi Experiment with the design of the one group pretest posttest design.(Swarjana 2015). Respondents in this study were women of childbearing age with high risk. Result: The results of the Wilcoxon Test showed that there was a difference in the score of knowledge and attitude of mothers before and after being given an audio-visual media intervention with a significance value of 0.00 (p value <0.05). There is a change in the mother's behavior before and after the audio visual media intervention with a significance value of 0.046 (p value <0.05).Conclusion: There is the effect of providing health education with audiovisual media on the knowledge, attitudes and behavior of mothers in using contraception